Development and evaluation of indices to assess the ecological health of the Pahang River, Malaysia - Adnan, Mohd Shalahuddin (2011)
Water is the essential need for life and all living things need water for living. Recently, the demand for clean and portable water has increased tremendously due to the rapid development and population growth. Since Malaysia has transformed from agriculture country to industrial based country, we are grappling with so many problems such as the increasing of waste, deterioration of water quality, and so on. Due to inadequate technical knowledge, we are not capable to handle and manage the increasing amount of waste. As a result, increasing amount of waste has polluted the water, degraded the habitat as well as caused a massive mortality of fish. Practically in Malaysia, assessment methods were focusing only on certain perspectives, e.g. chemical and physical parameters of water. The integrated assessment (combination between physical, chemical and biological component) to evaluate the health of aquatic environment is scarce. Furthermore, no specific and comprehensive assessment approach was established. For instance, water quality assessment is normally solely based on chemical and physical factors, while biological factor is neglected. This method only provides a partial perspective of water degradation. Moreover, it does not provide any information regarding biota status which becomes one of the main limitations of this method. The main focus of present dissertation is the development of assessment method that could show more sensitivity towards the biological assemblage and at the same time it also could provide additional information to decision maker prior initiating any restoration works. Understanding the effects only from physicochemical parameters is not adequate to evaluate the condition of water environment because it involved the biota. At present, few studies were conducted in this river to evaluate the environment condition of this river, however, none of them focused on the developing of bio-assessment method to evaluate the biotic and abiotic condition in the river. Thus, the present study was designed to investigate the fish composition, assess the water and habitat quality, and integrate this information to develop comprehensive assessment method that is reliable, rapid manner and the results can be easily deliver and present to public. In addition, the development of this assessment is crucial for monitoring and managing our water environment where the threats of biodiversity are tremendously increased especially this river.